Timber arch bridges with V-shaped hangers - Crocetti, Roberto (2019)
Thearch is a very efficient load bearing structure, especially when itsshape is affine to the funicular of forces. However, if live loads are predominant as compared to permanent uniformly distributed gravity loads,the arch will be subjected to substantial bending moments, thus losing a great part of its structural efficiency. In traditional arch bridges with hangers arranged in a vertical manner, asymmetrical loads would cause a substantialdeviation of the pressure line from the axial line of the arch.In this paper,an innovative concept for timber arch bridges is introduced where V-shaped hangers, rather than vertical hangers, are used. The adoption of V-shapedhangers significantly contributesto the reduction of the eccentricity between the pressure line and the axial line of the arch, thus decreasing the magnitude of bending moments in the arch.The paper discussesthe advantages of using V-shaped hangers as an alternativetovertical hangers, both in terms ofstatics, in-plane stabilityand dynamic efficiency. Moreover, the design and the recent construction of a parabolic three-hinged archmade of timber, with a steel V-shaped hangeris thoroughly discussedin the paper